PENGEMBANGAN MODUL BERMUATAN NILAI RELIGI (STUDI KASUS DI DAYAH TRADISIONAL PROVINSI ACEH) - Sulastri Sulastri; Mawaddah Mawaddah; Evendi Evendi (Majelis Pendidikan Aceh, 2022)
The development of the module has been studied in order to characterize the steps of development up to the feasibility test of the developed module. This study employs a qualitative and quantitative approach with R&D approaches based on a 4D model (Define, Design, Development, and Desseminate). The religious virtue presented exclusively refers to one of the Prophet Muhammad's four traits, Amanah. The sample approach utilized is called purposive sampling. This study's subjects were students from class XI IPA 1, with 5 male pupils and 28 female students. The results revealed that the developed module met the eligibility standards, including a mean content validity of 98.15 percent very valid category, a construct validity of 100 percent very valid category, a language validity of 71.43 percent quite valid category, and an overall average of the three validities of 93.54 percent very valid category. As a result, the thermochemical module with religious values can be employed in the chemistry learning process.